CHILDREN’S EMOTIONAL DEVELOPMENT IN A BROKEN HOME ENVIRONMENT: AN ELIZABETH B. HURLOCK PERSPECTIVE - Desty Survia; Rusyana Benyamin (Magistra, 2024)
Family is the most important primary group in society. The family is also a group formed from a relationship (conception) of men and women who have been bound in a marriage, lasting a long time to create and raise children or offspring in a family, consisting of a father, mother, and the presence of children. Different from families who experience divorce or broken homes children are only in the care of one of the parents and fulfill the role of parents who cannot run properly in caring for and educating children. This can affect the character of the child. Character is closely related to emotions. This study aimed to determine the emotional development of a child from a broken home family. The subject of this study was a 7-year-old boy from a broken-home family. This study used a descriptive qualitative method with several informants: the homeroom teacher, the mother (parent), and the child itself. The techniques used in data collection include observation, interviews, and documentation. This study shows that parents (mother/father) other family members (grandparents, aunts, uncles) also teachers play a role in children's daily lives. The results of this study can resemble and represent the contribution of parents and teachers in building children's emotions from broken homes